Antimicrobial potential of routine disinfectants agents used in health care units against opportunistic pathogenic bacterial species - Costa, Ana; Silva, Gustavo; Forti, Karine; Cardoso, Lívia; Batista, Rodrigo; Nunes, Shaulo; Hofling, José; Maia, Flávia; Wijesinghe, Gayan; Naveed, Hassan; Stipp, Rafael; Graner, Renata; et al. (Revista dos Trabalhos de Iniciação Científica da UNICAMP, 2019)
Biofilms are surface attached, matrix embedded micro-organisms. Biofilms are difficult to eradicate since Biofilm structure prevents the penetration of chemical agents and makes more resistant to antimicrobials. This research evaluate the efficacy routine chemical agents in removing bacterial biofilms. Agar well diffusion, MIC and MBC evaluate the efficacy against planktonic bacteria. Post-exposure biofilm biomass was quantified using CV assay. All disinfectants tested effectively eradicate biofilms and planktonic bacteria, whereas 2% chlorhexidine diclogunate and 2% sodium hypochlorite demonstrate highest efficacy.